2017
DOI: 10.4236/msa.2017.813075
|View full text |Cite
|
Sign up to set email alerts
|

Study the Influence of UV-Irradiation on the Photo Stability of Pure and Plasticized Poly (4-Vinyl Biphenyl) in Solid Films

Abstract: The effect of UV irradiation and blending with phthalate and terephthalate plasticizers on the photo-stability of Poly (4-vinyl biphenyl) was studied at different intervals of irradiation time and in presence of air. The increase in irradiation time on the photodegradation of polymer thin films caused a change in the intensity and shape of the fluorescence band. It has been found that the stability of the polymer decreases with the increase of irradiation time, and to increases with the increase of the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…In an earlier study, it has been reported that irradiation of polystyrene solid films resulted in changes in many bands in the FT IR spectra [9], and also was noticed in the irradiated pure and blended poly (fluoro styrene) isomers with phthalate and terephthalate plasticizers in solid films [24,25]. The same observation was noticed in the irradiation of poly (4-vinyl biphenyl) solid films [41].…”
Section: Ft-ir Spectra For Non-irradiated and Irradiated Pure And Blesupporting
confidence: 60%
“…In an earlier study, it has been reported that irradiation of polystyrene solid films resulted in changes in many bands in the FT IR spectra [9], and also was noticed in the irradiated pure and blended poly (fluoro styrene) isomers with phthalate and terephthalate plasticizers in solid films [24,25]. The same observation was noticed in the irradiation of poly (4-vinyl biphenyl) solid films [41].…”
Section: Ft-ir Spectra For Non-irradiated and Irradiated Pure And Blesupporting
confidence: 60%
“…As for the nature of the quenching itself, when considering the characteristics of the absorption spectra for DMPs [23] and for the imidazolate species forming the modified ZIF (UV absorption spectra, Figure S11 in the Supporting Information) suggests that they do not absorb at the wavelengths involved in the fluorescence spectra (excitation at 288 nm and emission of the imine within the Z8P ZIF between 400 and 540 nm (Figure S10a in the Supporting Information)). Therefore, it must be assumed that the quenching is not due to quenching effects by absorption of the emitted radiation by the imine.…”
Section: Resultsmentioning
confidence: 99%